A multicentre validation of Metasin: a molecular assay for the intraoperative assessment of sentinel lymph nodes from breast cancer patients. Issue 6 (4th January 2016) - Sai‐Giridhar, Priya; Al‐Ramadhani, Salma; George, Dilushana; Gopinath, Preethi; Andrews, William; Jader, Samar; Brown, Shelley; Findlay, Alison; Arkoumani, Evdokia; Al‐Sam, Salam; McKenzie, Jolanta G; Bradpiece, Howard; et al.
Abstract : Aims: Treatment strategies for breast cancer continue to evolve. No uniformity exists in the UK for the management of node‐positive breast cancer patients. Most centres continue to use conventional histopathology of sampled sentinel lymph nodes (SLNs), which requires delayed axillary clearance in up to 25% of patients. Some use touch imprint cytology or frozen section for intraoperative testing, although both have inherent sensitivity issues. An intraoperative molecular diagnostic approach helps to overcome some of these limitations. The aim of this study was to assess the clinical effectiveness of Metasin, a molecular method for the intraoperative evaluation of SLNs. Methods and results: RNA from 3296 lymph nodes from 1836 patients undergoing SLN assessment was analysed with Metasin. Alternate slices of tissue were examined in parallel by histology. Cases deemed to be discordant were analysed by protein gel electrophoresis. There was concordance between Metasin and histology in 94.1% of cases, with a sensitivity of 92% [95% confidence interval (CI) 88–94%] and a specificity of 97% (95% CI 95–97%). Positive and negative predictive values were 88% and 98%, respectively. Over half of the discordant cases (4.4%) were ascribed to tissue allocation bias (TAB). Conclusions: Clinical validation of the Metasin assay suggests that it is sufficiently sensitive and specific to make it fit for purpose in the intraoperative setting.